THE ROLE OF ISLAMIC SPIRITUALITY IN PREVENTING BURNOUT IN UNIVERSITY STUDENTS - Mutmainah, Elsa; Tryzulhijah, Riana; Alfian, Ripan; Fajrussalam, Hisny (The Pontianak State Institute of Islamic Studies, 2025)
The purpose of this study is to analyze whether there is a role of Islamic spirituality in preventing burnout in college students as well as the relationship between Islamic spirituality and burnout. The research method used is this research design using a descriptive qualitative approach. With literature study and filling out questionnaires through g-forms as data collection methods. The results of this study indicate that there is a role of Islamic spirituality in preventing burnout in college students. This can be seen from the percentage level of Islamic spirituality, which is 52.5% in the good category, 32.5% in the very good category. 12.5% are in the good enough category, and only 2.5% are in the bad category. While the burnout level shows that 35% are in the very good category, and 37.5% are in the good category, 17.5% are in the good enough category, while the rest, namely 7.5% and 2.5% are in the bad and very bad categories. This shows that the higher the level of one's Islamic spirituality, the lower the level of burnout in a person. In addition, there is a relationship between Islamic principles such as tawakal, prayer and dhikr, time management and life balance (Wasathiyah), patience and gratitude which have a relationship with Burnout. Islamic spirituality has a role in preventing burnout in students who are used as coping in dealing with various pressures and difficulties.